Current and recalled symptoms of Attention Deficit Hyperactivity Disorder in parents of children with ADHD - Hemamali Perera; Numega Jaysuriya; Chandima Jeewandara (Sri Lanka Journal of Psychiatry, 2011)
Background Attention deficit hyperactivity disorder (ADHD) has a strong genetic aetiology and high heritability. Biological relatives of children with ADHD have a substantial risk of developing this disorder. Accordingly, parents of children with ADHD are likely to have more symptoms of ADHD. Diagnosing ADHD in adults is hampered by lack of agreement on diagnostic criteria. Aims To test the hypothesis that parents of children with ADHD have higher prevalence of ADHD symptoms when compared to a control group of parents. Methods Presence of ADHD symptoms in parents were assessed using the Adult ADHD Self-Report Scale (ASRS) to elicit current symptoms and the Wender Utah scale to elicit retrospectively recalled symptoms from childhood. The study group comprised of parents of consecutive attendees of specialist clinics for children with ADHD at a tertiary care institution. Control group was randomly selected from parents of children attending general paediatric clinics. Presence of current ADHD symptoms was assessed using Adult ADHD Self- Report Scale (ASRS). The Wender Utah scale elicited retrospectively recalled symptoms from childhood. Results Study group consisted of 117 parents and the control group of 69 parents. Prevalence of ADHD symptoms was higher in the study group, compared to the control group (21.3% vs 4.3% on ASRS and 11.9% vs 0% on Wender Utah scale). The odds for having ADHD symptoms in parents of children with ADHD were 5.9, compared to the control group. Correlation of scores on the two scales was high in the study group (0.78) and less in the control group (0.44). Conclusion The study shows a high prevalence of symptoms of ADHD in parents of children with ADHD. Further research is indicated to investigate the implication of the findings of this study. DOI: http://dx.doi.org/10.4038/sljpsyc.v2i1.3161 SL J Psychiatry 2011; 2 (1): 18-22